1988
DOI: 10.1080/00039896.1988.9934367
|View full text |Cite
|
Sign up to set email alerts
|

Role of Dehydration in Heat Stress-Induced Variations in Mental Performance

Abstract: Variation in mental performance under different levels of heat stress-induced dehydration was recorded in 11 subjects heat acclimatized to the tropicals. Dehydration was induced by a combination of water restriction and exercise in heat. The psychological functions--arithmetic ability, short-term memory, and visuomotor tracking--were assessed in a thermoneutral room after the subjects recovered fully from the effects of exercise in heat, as reflected by their oral temperature and heart rate. The results indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
219
3
2

Year Published

2001
2001
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 310 publications
(227 citation statements)
references
References 3 publications
3
219
3
2
Order By: Relevance
“…At the same time, ratings of tiredness and headache increase (Figure 1). There are also some indications in the published literature that cognitive function, as assessed by decision making and reaction time tests, is also impaired at relatively low levels of dehydration (Gopinathan et al, 1988). This may be important when decisions have to be made or where judgement and skill are involved; driving a motor car is a good example of such a task.…”
Section: Hydration Status and Wellnessmentioning
confidence: 99%
“…At the same time, ratings of tiredness and headache increase (Figure 1). There are also some indications in the published literature that cognitive function, as assessed by decision making and reaction time tests, is also impaired at relatively low levels of dehydration (Gopinathan et al, 1988). This may be important when decisions have to be made or where judgement and skill are involved; driving a motor car is a good example of such a task.…”
Section: Hydration Status and Wellnessmentioning
confidence: 99%
“…Resulting data indicated a significant correlation between cognitive dysfunction and severity of dehydration. Subjects exhibited progressive impairment in mathematical ability, short-term memory and visuomotor function once 2% body fluid deficit was achieved (Gopinathan et al, 1988). Cian et al (2000) demonstrated impaired long-term memory following dehydration resulting from heat stress.…”
Section: Pathophysiologymentioning
confidence: 99%
“…Gopinathan et al (1988) examined changes in cognitive function in 11 healthy adult subjects under varying degrees of dehydration induced by a combination of water restriction and heat stress. Resulting data indicated a significant correlation between cognitive dysfunction and severity of dehydration.…”
Section: Pathophysiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, substantial evidence exists in the observation of decreased cognitive function when dehydrated by ≥ 2% body mass loss, with decreases in self-rated alertness and perceived tiredness being reported [14,15]. More specifically, within military personnel, dehydration of ≥ 2% has a negative effect on morale, willingness to work and overall mental performance [16]. In a military environment whereby optimal physiological and cognitive functioning are vital, impairments can not only reduce performance but may also ultimately cost lives.…”
Section: Introductionmentioning
confidence: 99%